Enantioselective, Copper-Catalyzed Addition of Nucleophilic Silicon to Alkenyl-Substituted Phosphine Oxides - Hong, Dou; Mao, Wenbin; Irran, Elisabeth; Oestreich, Martin (Synthesis, 2022)
An enantioselective β-silylation of α,β-unsaturated phosphine oxide derivatives using a silylboronic ester as the silicon pronucleophile is reported. The reaction is catalyzed by copper salts in the presence of chiral pyridine–oxazoline (PyOx) ligands. Good to high enantioselectivities (≤95% ee) are obtained for β-aryl-substituted acceptors whereas alkyl residues in the β-position led to a lower ee value for 1° and no reaction for 2° and 3°. The new method represents another way of accessing α-chiral silanes and complements the known β-borylation.
Keywords: asymmetric catalysis; conjugate addition; copper; phosphorus; silicon; silylation